Relevansi Dokumen Abu Dhabi terhadap Pelayanan Seksi Hubungan Antaragama dan Kepercayaan di Paroki Bunda Maria Cirebon - Yosepa Angela Siregar; Fransisca Romana Wuriningsih; Yustinus Joko Wahyu Yuniarto; Anselmus Joko Prayitno (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2025)
Indonesia's diversity is a necessity to be denied, the deep-rooted Plurality must be maintained. Bhinneka Tunggal Ika and Pancasila as the breath and pulse of the nation must be lived and live for the nation. Diversity as a gift of God is an extraordinary potential, but it is necessary to be aware of the potential for conflict, tearing the weaving of the golden thread of plurality. The Holy Father's apostolic trip to the UAE gave birth to a brotherhood document, an invitation to cooperation and interfaith dialogue with Imam Al Azhar Ahmad el-Tayeb. Similarly, what happened in Our Lady of Cirebon Parish as a research locus. According to the doctrinal teaching, the Church voices the placement of others as brothers. This qualitative method research aims to explore the relevance of Abu Dhabi documents to the services of Interfaith Relations and Parish Beliefs, the practice of religious moderation of the people, inhibiting factors, supporting factors, efforts to encourage supporting factors, and suppressing inhibiting factors. Data were obtained through in-depth interviews with fourteen informants consisting of Catholics, representatives of each religion in Cirebon, representatives of Sundanese Wiwitan believers, and cultural experts using purposive sampling, observation, and documentation techniques. The results of the data show that twelve focuses of the Abu Dhabi document brotherhood have been applied in the service of the Sie Interfaith Relations and Parish Beliefs but have not been maximized and continue to be sought to be intact. Fanaticism, lack of team cohesiveness, and fear of the people are inhibiting factors. The Church has supported since the Second Vatican Council echoed interfaith cooperation. The Pastoral Focus of the Diocese of Bandung is a supporter in this study. So the effort is to initiate activities with fraternal nuances, and the role of the parish pastor in his pastoral mutual aid is to introduce documents to the grassroots. The answer to this study proves that the people of Cirebon can live harmoniously side by side with different ones. In line with the manuscript of Serat Carub Kandha through a philological approach, as a collective memory of the ancestral heritage in building a harmonious Cirebon.